Biodiesel production using unrefined methanol as transesterification agent and the research of individual effect of impurities. (15th March 2015) - Ma, Yingqun; Wang, Qunhui; Zheng, Lu; Gao, Zhen; Yang, Yajuan; Wang, Nan; Ma, Hongzhi
Abstract: In this study, we produced biodiesel by utilising waste cooking oil as a raw material, unrefined methanol produced by a chemical plant as a transesterification agent and sodium hydroxide as a catalyst. The yield and heating value of the biodiesel produced with unrefined methanol were respectively 1.09% and 0.23 MJ/kg higher than those of the biodiesel prepared with pure methanol. The biodiesel characteristics met the standard of the ASTM (American Society for Testing and Materials). We investigated the effects of four impurity types in the unrefined methanol on biodiesel preparation. Alcohol impurities acting as co-solvents and transesterification agents can increase the yield and heating value. Organic solvent impurities can only act as co-solvents; thus, they can only improve the yield. Ester impurities (methyl formate) exhibited no effects on the yield and heating value because they evaporated in the ester exchange reaction. Water impurities significantly reduced the yield by affecting the miscibility of waste cooking oil and pure methanol. However, the negative effects of these impurities were alleviated when water was mixed with the organic solvent impurities. This study has a great significance for the resource and energy of unrefined methanol. Highlights: Unrefined methanol used as transesterification agent to prepare biodiesel. Effects of four impurity types in the unrefined methanol was investigated. Water has important impact to the biodiesel yield.